Exploring Positive Humor as a Leadership Tool: A Biblometric Review - Syaifussalam, Muhammad; Saikhoni, Saikhoni; Wilantika, Rima (Bulletin of Counseling and Psychotherapy, 2025)
The concept of positive humor is one way to manage stress during work so that employees can be fully involved in work. The paper aims to provide a broad bibliometric literature review of 'leader positive humor'. Articles were obtained through Publish or Perish (PoP) software with the Google Scholar database. 53 out of 81 articles found in the Google Scholar database from 2018 to 2023 were analyzed in this research. Selected references are then managed using reference management software, namely Zotero. After managing the database, this research classifies and visualizes it using VOSviewer software. This review provides an appropriate reference for further research on 'leader positive humor'. Hopefully, this research can contribute to scientific development in industrial and organizational psychology, especially on the topic of 'leader positive humor'.